What Matters for Life Satisfaction of University Students: the Role of Social Capital and Self-efficacy? - zhang, xiaomei; Ju, Soon-Yew (South Asian Journal of Social Sciences and Humanities, 2023)
The purpose of this article is to look at the life satisfaction of university students in the Chinese city of Ji'nan. Because of the vital importance of university students, their life satisfaction is valuable and should be investigated. The literature on students' life satisfaction leaves the three factors in the study unexplored. As a result, this research attempts to explain the relationship between university students' life satisfaction and individual social capital through the mediating influence of self-efficacy, which may be a novel conceptual model rarely used in prior studies, particularly in Ji'nan, China. The results indicates that the significant positive association of individual social capital with life satisfaction for university students with the mediating effect of self-efficacy. As a non-experimental descriptive study approach, a quantitative (deductive reasoning) technique was utilized to quantify the issue, in which a survey questionnaire was used to collect numerical data, which was then converted into a table.
Keywords: individual social capital; self-efficacy; life satisfaction; social capital; university students